DETERMINAN PROFITABILITAS PADA BANK PEMBIAYAAN RAKYAT SYARIAH DI INDONESIA - Uus Ahmad Husaeni (Jurusan Akuntansi Politeknik Negeri Bandung, 2017)
Abstract: The purpose of this study is to examine the factors that affect the profitability in Islamic rural bank in Indonesia. The analytical tool used in this research is multiple linear regression analysis. The results of the study, to simultaneously show that the Third Party Funds, Capital Adequacy Ratio, Financing to Deposit Ratio Non Performing Financing and Operating Expanse to Operating Income (BOPO) significantly affects to Return on Asset (Profitability), while the rest is explained by other factors not enrolled in this study. Keywords: Financing, Internal Factors; Islamic Rural Banks, Multiple Regression